PERLINDUNGAN HUKUM DEBITUR DALAM EKSEKUSI JAMINAN FIDUSIA SETELAH PUTUSAN MK NOMOR 2/PUUXIX/2021 - UTOMO, DARMAWAN TRI BUDI; DEWI, MIEKE ANGGRAENI; WIDYAWATI, AGNES MARIA JANNI (Universitas Mahasaraswati K. Mataram, 2024)
This research will attempt to provide an analysis regarding the Legal Protection of Debtors in Fiduciary Guarantee Execution both before and after the Constitutional Court Decision Number 18/PUU-XVII/2019. This study employs the juridical normative legal research method, with secondary data being utilized, which consists of pre-existing data. The analytical technique employed is descriptive analytical analysis. The research findings indicate that the Legal Protection of Debtors in Fiduciary Guarantee Execution before the Constitutional Court Decision Number 18/PUU-XVII/2019 Equalizing the fiduciary guarantee certificate in Article 15 paragraph (2) and (3) of the Fiduciary Law resulted in the constitutional rights of debtors being infringed upon. The Fiduciary Receiver (creditor) may carry out execution in the form of private sale of the fiduciary collateral objects pursuant to Article 29 paragraph (1) letter c in conjunction with paragraph (2) of the Fiduciary Law based on an agreement between the fiduciary grantor and the fiduciary receiver. In POJK Number 29 of 2014 Article 14, creditors are prohibited from withdrawing fiduciary collateral objects, with conditions stipulated in the fiduciary law also being agreed upon by the parties in the agreement. The execution of fiduciary collateral objects must be based on the determination that the debtor has defaulted and cannot be unilaterally permitted by the creditor, in the a-quo decision of the Constitutional Court, the creditor is not allowed to forcibly withdraw unilaterally, even though the creditor has a fiduciary guarantee certificate. The creditor and debtor parties must agree in advance on the existence of default as stipulated in the agreement